Formulation and evaluation of transdermal composite f ilms of chitosan-montmorillonite for the delivery of curcumin - Thakur, Garima; Singh, Amrinder; Singh, Inderbir (International Journal of Pharmaceutical Investigation)
Composite transdermal films of chitosan (CS)/montmorillonite K 10 (MMT) clay were prepared for the delivery of curcumin. CS/MMT films were evaluated for various physicochemical parameters. The films were characterized by Fourier transform infrared spectroscopy and X-ray diffraction analysis. Water uptake and swelling ratio of the films was found to decrease with increase in concentration of clay. Mechanical properties of the films were assessed in terms of tensile strength and extensibility using texture analyzer. Increase in tensile strength and reduction in extensibility was reported with increase in the clay content. This was attributed to the formation of intercalated structure and restriction in mobility of CS polymeric chains with the inclusion of clay particles. In vitro drug release study on transdermal films indicated pronounced sustained release of curcumin by the incorporation of clay particles in the CS polymer matrix. Stability study indicated no significant effect on physicochemical properties of films kept at 40°C and 75% RH for 3 months. Overall CS/MMT composite transdermal films exhibited improved mechanical and sustained drug release properties.
Keywords: Chitosan; chitosan/montmorillonite composites; curcumin; montmorillonite K 10; trasdermal fims